Perceived Organizational Support and Job Satisfaction as Factors in the Happiness of Police Members at Work - Aulia, Aulia; Dania, Reiska Rahma (Empathy : Jurnal Fakultas Psikologi, 2023)
Persepsi Dukungan Organisasi dan Kepuasan Kerja sebagai Faktor Kebahagiaan Anggota Polri di Tempat KerjaHappiness is one of the important things in human life, including in work life. Working without having a sense of happiness at work will have an impact on individual or organizational performance. Therefore, examining the factors that may contribute to high or low happiness at work is something that is important to study. This study aims to examine the role of perceived organizational support and job satisfaction on the happiness of Polri members at work. The population of this study were active members of the police in the working area of Indonesia with a sampling technique using quota sampling, namely as many as 400 members of the Indonesian National Police. The approach used in this study is quantitative with the correlation method. The data collection tool used the happiness scale at work, the perceived organizational support scale and the job satisfaction scale. The results of the data analysis showed that the coefficient obtained was R=0.551, F=86.494, p=0.000 (p<0.01). The findings conclude that perceived organizational support and job satisfaction have a role in the happiness of Polri members at work.